Analysis of Adult Hippocampal Neurogenesis in Neurodegenerative disease - GANG HAN (2022)
Neurodegenerative diseases cause severe health and social problems. They create a health and economic burden on individuals and their families. Currently, there is no efficient treatment, apart from some attenuating medicines, for the majority of neurodegenerative diseases. Neurone loss is a consistent characteristic of these diseases. The hippocampal dentate gyrus is one of the regions in the adult mammalian brain capable of generating new neurones throughout life. The neurogenic niche appears to play an important role in the neuronal dysfunction associated with neurodegeneration. However, the detailed mechanisms underpinning this process are still unclear. To explore the neurogenic niche in Frontal Temporal Dementia (FTD) and Parkinson’s disease (PD) we investigated disease-relevant rodent models and donated post-mortem human brain samples. Immunohistochemistry and immunofluorescent assays were developed to allow the quantification of dividing cells and immature neurones in the adult hippocampus of selected tissues. The TDP43-Q331K knock-in mice, a model of FTD, revealed a significant reduction in the number of dividing cells (Ki67+) and immature neurones (Dcx+). Distinct morphological stages of immature neurone development were observed in this disease model. Further rodent neurotoxin-based models were used to characterise neurogenesis in PD. However, contrary to previous reports, these models did not consistently induce significant deficits in adult hippocampal neurogenesis (AHN). Human post-mortem brain samples were used to explore the neurogenic niche, but we were unable to consistently observe immature neurones in non-diseased brain samples. In summary, this project identified significant AHN deficits in the FTD mouse model. These require further analysis to determine their function and possible role in human disease.